Dynamical Balance and Verification of a Rotor System Based on Sensitivity Analysis - Luo, Zhong; Wei, Yanhui; Hou, Xiaojie; Wang, Fei (Journal of Vibration Testing and System Dynamics, 2026)
In allusion to the unbalanced vibration of rotor system, sensitivity analysis and balance method of rotor system were studied. Based on rotor dynamics, combined sensitivity analysis with the balancing methods of three trial weight and modal, a hybrid method was proposed which can be balanced without phase information. Firstly, the model of rotor was established by the finite element method and the correction plane is selected by the sensitivity analysis. Furthermore, the balance speed is determined according to the modal equilibrium theory and the weight calculation is conducted by the balancing method of three trial weight Finally, a dynamic balance experiment was carried out on the rotor model test station. The results of simulation and experiment show that the proposed balance method can not only effectively reduce the residual vibration of rotor, but avoid the blindness of selecting the correction plane and balance speed by the traditional balance method, which is expected to improve the balance efficiency.